Anthocyanin profile of Syzygium oleana young leaves and fruits using triple quadrupole mass spectrometer: Identification of a new peonidin - Tuty Anggraini; Daimon Syukri; Thammawong Manasikan; Kohei Nakano (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Anggraini T, Syukri D, Manasikan TW, Nakano K. 2020. Anthocyanin profile of Syzygium oleana young leaves and fruits using triple quadrupole mass spectrometer: Identification of a new peonidin. Biodiversitas 21: 5893-5900. Anthocyanin is pigment present in many red, blue and purple colored plants that can be used as stable food-safe colorings and also offer health benefits as antioxidants. Syzygium oleana, with its dark purple fruit and red leaves, is one hitherto unexplored source of anthocyanin. This study is the first to establish the anthocyanin profile of S. oleana leaves and fruit exploiting the speed and accuracy of Multiple Reaction Monitoring (MRM) with a triple quadrupole mass spectrometer. The anthocyanin compounds in the leaves and fruit of S. oleana were found to be derivatives of agliconpeonidin, cyanidin derivative, delphinidin. It was found that while both leaves and fruit of S. oleana contain the anthocyanin precursors cyanidin, delphinidin, petunidin, and peonidin. Fruit contains the anthocyanin malvidin and a large amount of petunidin not present in the leaves. In detail: anthocyanin found in S. oleana leaves were Cyanidin 3-galactoside, cyanidin with m/z 611, Delphinidin 3-O-?-D-glucopyranoside, and unknown peonidin. Anthocyanin in S. oleana fruits was cyanidin with m/z 449.1, delphinidin 3-O-?-D-glucopyranoside, petunidin with m/z 476, Malvidin 3-O-?-D-glucopyranoside, and an unknown peonidin. Fruit could be a better anthocyanin source and more effective as colorant than leaves, while leaves contain a stronger as yet unidentified antioxidant.